An Option or Necessity: Can the ‘Informal’ and ‘Formal’ Co-Exist Within Higher Education? - Ian Jones (Youth)
In further understanding the importance of the informal/formal nexus, it is posited that they can co-exist, as explained in the case description example of a Youth Professional Practitioner Network (YPPN). It posits the influence of ‘informal education’ that creates the opportunity for value-based notions such as respect in enabling individuals to form trusting relationships. Through such relationships, the possibility of a ‘community of practice’ is formed. Such notions are argued to be inherent within the YPPN. In presenting such discussions in the exploration of this question, it poses the argument that it is possible and is more of a necessity.